Sustainability lies in the soil - Simmons, Robert W.; Tole, Jonathan (Research Publishing International, 2017)
An experimental system developed in partnership by vegetable growers Produce World Ltd’s Mr Jonathan Tole and Cranfield University’s Senior Lecturer in Sustainable Soil Management, Dr Robert Simmons, is poised to revolutionise the way farmers manage their soils. Together, the researchers are unlocking the potential of soils through the new science of agri-informatics and their innovative, collaborative Soil-for-Life® management system.